ANALYSIS OF RELIGIOUS TOURISM OBJECTS IN JOMBANG REGENCY USING COG METHOD - Muhammad Kamal Abdun Nasir; Meriana Wahyu Nugroho (Universitas Islam Malang, 2022)
Jombang Regency is a religious tourism area where many national scholars are buried here so that Jombang becomes a tourist spot for tourists in various regions in Indonesia, with these objects tourists need a map to make it easier when visiting Jombang Regency. The purpose of this study was to analyze the distribution of thematic maps and to observe the supporting facilities for religious tourism infrastructure including (Tomb of KH. Abdur Rahman Wahid, tomb of KH. Bisri Syansuri, tomb of KH. Wahab Hasbullah, tomb of KH.Mustain Romlly and Tomb of Syayid Sulaiman) . This study uses digitized coordinates that produce a map of the distribution of religious tourism objects, for the application of a Geographic Information System (GIS) and questionnaires distributed to six religious tourism objects, using the Center Of Gravity (COG) method to determine the intended route. The results of the study obtained six coordinates of religious tourism objects and resulted in a distributed questionnaire declared valid and reliable with Cronbach's alpha value of 0.809 for the Geographic Information System indicator and 0.933 for the Center of Gravity indicator.